Implementation of Project-Based Learning Model to Improve Student Creativity in Chemistry Subject at SMA Negeri 1 Bakongan Timur - Iskandar; Rahman, Eka (DEEP LEARNING: Journal of Educational Research, 2025)
This study examines the application of the Project-Based Learning (PjBL) model to enhance students' creativity in chemistry at SMA Negeri 1 Bakongan Timur. This study was conducted to address the challenges faced by students in demonstrating creative thinking and problem-solving skills during chemistry learning, which often relies heavily on memorization. This study used a classroom action research design implemented in two cycles, each consisting of planning, implementation, observation, and reflection. Participants were 11th-grade students, who were actively involved in project-based activities designed to connect chemistry concepts with real-life applications. Data were collected through observation sheets, documentation of student activities, and a creativity assessment rubric. The study findings indicated that the implementation of the PjBL model significantly enhanced students' creativity as reflected in their ability to generate original ideas, design innovative experiments, and present their projects creatively. Improvement was observed from cycle I to cycle II, where the percentage of students achieving high levels of creativity increased substantially. The results indicate that PjBL not only enriches the learning experience but also fosters independent and critical thinking skills. Therefore, PjBL is recommended as an effective learning model to enhance creativity in chemistry education.